Fast Differential Analysis of Propolis Using Surface Desorption Atmospheric Pressure Chemical Ionization Mass Spectrometry - Xue-yong Huang; Xia-li Guo; Huo-lin Luo; Xiao-wei Fang; Teng-gao Zhu; Xing-lei Zhang; Huan-wen Chen; Li-ping Luo (International Journal of Analytical Chemistry)
Mass spectral fingerprints of 24 raw propolis samples, including 23 from China and one from the United States, were directly obtained using surface desorption atmospheric pressure chemical ionization mass spectrometry (SDAPCI-MS) without sample pretreatment. Under the optimized experimental conditions, the most abundant signals were detected in the mass ranges of 70 to 500 m/z and 200 to 350 m/z, respectively. Principal component analyses (PCA) for the two mass ranges showed similarities in that the colors had a significant correlation with the first two PCs; in contrast there was no correlation with the climatic zones from which the samples originated. Analytes such as chrysin, pinocembrin, and quercetin were detected and identified using multiple stage mass spectrometry within 3 min. Therefore, SDAPCI-MS can be used for rapid and reliable high-throughput analysis of propolis.